2015
DOI: 10.1210/jc.2014-3018
|View full text |Cite|
|
Sign up to set email alerts
|

Central Insulin Administration Improves Odor-Cued Reactivation of Spatial Memory in Young Men

Abstract: These findings suggest that acute intranasal insulin improves odor-cued reactivation of spatial memory in young men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 44 publications
1
45
1
Order By: Relevance
“…By causing a significant reduction in the AHP, we predict insulin may be able to enhance cellular excitability in aging and offset cognitive decline. Indeed, several clinical studies have provided robust evidence that increasing brain insulin availability through intranasal delivery of the hormone is able to enhance recall in young subjects [76; 77] or MCI patients [78; 79; 80]. Similarly, we have shown beneficial effects of intranasal insulin on memory recall in aged animals in the Morris water maze [74].…”
Section: The Impact Of Disappearing Hormones In the Brain Of Aged mentioning
confidence: 59%
“…By causing a significant reduction in the AHP, we predict insulin may be able to enhance cellular excitability in aging and offset cognitive decline. Indeed, several clinical studies have provided robust evidence that increasing brain insulin availability through intranasal delivery of the hormone is able to enhance recall in young subjects [76; 77] or MCI patients [78; 79; 80]. Similarly, we have shown beneficial effects of intranasal insulin on memory recall in aged animals in the Morris water maze [74].…”
Section: The Impact Of Disappearing Hormones In the Brain Of Aged mentioning
confidence: 59%
“…This contradicts reports of enhanced memory in healthy human subjects after insulin IND [27, 44, 65]. Insulin IND has been shown to be an effective treatment for mild cognitive impairment and Alzheimer’s disease (AD) [43, 66].…”
Section: Discussionmentioning
confidence: 98%
“…Beyond altered Kv1.3 phosphorylation state, insulin IND also induces behavioral modifications, as evident by enhanced object memory recognition and increased performance in the two-odor discrimination task. [16, 2527]. These studies demonstrate insulin’s ability to influence MC activity [18, 20] and therefore olfactory functioning [16, 28].…”
Section: Introductionmentioning
confidence: 96%
“…refs 1618). Studies on cognitive effects indicate that hippocampal-dependent memory processes benefit particularly from intranasal insulin in humans 1924 . Similarly, rodent studies have shown that insulin plays an important role in regulating synaptic plasticity in the hippocampus 25, 26 .…”
Section: Introductionmentioning
confidence: 99%